IDENTIFICATION OF SELECTED POLYPHENOLS IN GRAPE (VITIS VINIFERA) LEAVES - I.R. Asqarov; M.M. Mo‘minjonov; S.L. Khakimov (Western European Studies, 2025)
Grape (Vitis vinifera) leaves have long been utilized in various traditional medical practices due to their wide spectrum of therapeutic properties. In addition to being a common dietary component in some cultures, grape leaves are known to contain a diverse array of bioactive compounds, particularly polyphenols, which are associated with antioxidant, antiinflammatory, and antimicrobial effects. This study focuses on the preliminary identification of selected polyphenolic compounds present in grape leaves and evaluates their potential pharmacological relevance. The chemical composition of the leaves was analyzed using spectrophotometric methods to determine the presence of key phenolic constituents. The findings contribute to a growing body of evidence supporting the ethnomedicinal use of grape leaves in the prevention and management of chronic diseases, including cardiovascular disorders, metabolic syndrome, and gastrointestinal ailments. Furthermore, the study emphasizes the importance of grape leaves as a sustainable natural resource with potential applications in functional food and phytopharmaceutical development.
Keywords: grape; grape leaf; chemical composition